Salmonella enterica, subspecies enterica, serotype Enteritidis Outbreak at a Lodge in Mokopane, Limpopo Province, January 2014 - Kuonza, Lazarus R. (University of Pretoria, 2015)
Dissertation (MPH)--University of Pretoria, 2014.